The story of the Gettysburg address - Richards, Kenneth G 1926- (Chicago Childrens Press, 1992)
Traces the events which led to the Battle of Gettysburg in 1864 and describes the dedication of the cemetery to the fallen soldiers by Lincoln in his famous speech. Includes text of the speech
American Corner
Includes index
11
Keywords: Freedom